Understanding Business Model of Digital Journalism in Indonesia - Masduki, Masduki; Prastya, Narayana Mahendra; Yusuf, Iwan Awaluddin; Ningsih, Ida Nuraini D. K. (Jurnal Kajian Jurnalisme, 2024)
The transformation in the media landscape in Indonesia is underscored by the emergence of digital-centric media entities and a new mode of news production distinctly divergent from traditional journalism. The purpose of this study is to examine the evolving business model of digital journalism, a sector experiencing rapid growth following the advent of the internet, social media, and the consolidation of online journalism since 2010. Employing a qualitative-descriptive method, this research is designed to capture the digital journalism business model in Indonesia's post-traditional print and broadcast media systems. From 2021 to 2023, the authors meticulously observed the contents and management of selected news media outlets, conducted semi-structured interviews, and gathered pertinent documents. The key question of this study centers on the nature of the business model underpinning journalism on digital platforms and its repercussions for the interest of news production and publication. The study reveals that business models for digital news media remain unstandardized, and the ecosystem of platform-based journalism has yet to achieve a healthy climate. From the perspective of digital news consumption, the prevailing culture of gratuitous (free) news culture and the concern of keeping trusted news media pose significant obstacles for news corporations in sustaining their operations.